(untitled) (Contemporary Journal of Social Science Review, 2025)
This research article, titled "Al-Durar al-Saniyya fi Tarajim al-Silsila al-Aliyya: Ahwal al-Mashaikh al-Suhrawardiyya," provides a comprehensive historical and biographical account of the Sufi masters belonging to the Suhrawardi order. The study meticulously traces the spiritual lineage (Silsila) starting from the Prophet Muhammad (PBUH) through the leading figures of the order, including Imam Shihab al-Din al-Suhrawardi, Bahauddin Zakariya Multani, and reaching contemporary mentors like Bashir Ahmad al-Madani. The author utilizes both "Mujmal" (concise) and "Mufassal" (detailed) approaches to document the lives, academic contributions, and spiritual practices of these luminaries. By examining rare manuscripts and authentic historical sources, the article highlights the role of these scholars in the dissemination of Islamic jurisprudence (Fiqh) and Sufism (Tasawwuf) across the Indian subcontinent and beyond. This work serves as a vital reference for understanding the spiritual heritage and the historical evolution of the Suhrawardi Sufi tradition.